1989
DOI: 10.1021/bi00445a029
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the pore-forming domain of colicin A with phospholipid vesicles

Abstract: The interaction of the 20-kDa pore-forming domain of colicin A with phospholipid vesicles was investigated by gel permeation chromatography, analytical centrifugation, and electron microscopy. Under the experimental conditions of this study, this peptide was found to interact only with vesicles containing negatively charged phospholipids. It forms a well-defined disklike complex with phosphatidylglycerols with a preference for those containing 12-14 atoms of carbon in their fatty acid chain. This complex has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…This constant, k, shows pH and negative charge density dependence identical to that observed using completely different experimental approaches (Pattus et al, 1983;Collarini et al, 1987;Massotte et al, 1989). The results obtained confirm the umbrella model for the spontaneous insertion of colicin A thermolytic fragment into vesicles, and the occurrence during this process of a "molten globule" intermediate.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…This constant, k, shows pH and negative charge density dependence identical to that observed using completely different experimental approaches (Pattus et al, 1983;Collarini et al, 1987;Massotte et al, 1989). The results obtained confirm the umbrella model for the spontaneous insertion of colicin A thermolytic fragment into vesicles, and the occurrence during this process of a "molten globule" intermediate.…”
supporting
confidence: 86%
“…Bromine atoms are known to quench the intrinsic tryptophan fluorescence of proteins. The mechanism of this quenching is probably collisional (East & Lee, 1982;McIntosh & Holloway, 1987;Yeager & Feigenson, 1990), although a distance-dependent quenching mechanism has recently been proposed (Bolen & Holloway, 1990). The introduction of bromine atoms at different positions along the fatty acid acyl chain of the phospholipid allows for the determination of the depth at which the fluorophore group of the protein is located within the bilayer (McIntosh & Holloway, 1987).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, such experiments do not allow one to compare the binding of Br,Ole,GroPGro and Ole,GroPGro to the colicin-A pore-forming domain. However, the value for Br,Ole,GroPGro is very close to that reported by Massotte et al, (1989), using gel chromatography and different lipids. They found that at a lipidprotein ratio of 33 and at acidic pH, all the protein was bound to 1,Z-dimiristoyl-sn-glycero-3-phospho-sn-glycerol (Myr,GroPGro), forming a complex.…”
Section: Irreversibility Of the Binding Of Colicin A To Brolegropgrmentioning
confidence: 57%
“…The lyophilized peptide was dissolved in the desired buffer and the solution was spun in an Eppendorf centrifuge for 15 min to remove suspended particles and nonsolubilized material. The thermolytic fragment concentration was determined from the absorbance at 280nm using the molar absorption coefficient (cZaO 2.43 X 104M-'cm-') determined previously (Massotte et al, 1989).…”
Section: Cell Growth and Purificationmentioning
confidence: 99%